Burkholderia cordobensis sp. nov., from agricultural soils. - Draghi, Walter Omar (2014)
Two Gram-negative, rod-shaped bacteria were isolated from agricultural soils in Co ́ rdoba province in central Argentina. Their 16S rRNA gene sequences demonstrated that they belong to the genus Burkholderia, with Burkholderia zhejiangensis as most closely related formally named species; this relationship was confirmed through comparative gyrB sequence analysis. Whole-cell fatty acid analysis supported their assignment to the genus Burkholderia. Burkholderia sp. strain YI23, for which a whole-genome sequence is available, represents the same taxon, as demonstrated by its highly similar 16S rRNA (100 % similarity) and gyrB (99.1?99.7 %) gene sequences. The results of DNA?DNA hybridization experiments and physiological and biochemical characterization further substantiated the genotypic and phenotypic distinctiveness of the Argentinian soil isolates, for which the name Burkholderia cordobensis sp. nov. is proposed, with strain MMP81T (5LMG 27620T5CCUG 64368T) as the type strain.